Study of Residual Stress State of Massif During Rock Destruction by an Explosion at The Limit Contour of a Quarry (International Journal of Scientific Trends, 2024)
The paper studies the residual stress state of the rock mass caused by the blast, which changes the residual stress-strain state and physical and technical properties of the rock mass outside the crushing zone. The paper presents the parameters of drilling and blasting operations, the main characteristics of destruction, the geological and mining factors that affect them, and also studies the physical picture of the explosive destruction of the rock mass.